Analysis of Using Tiktok as Live Marketing in Attracting Consumers' Interest in Buying - Ervi Nabila Siregar; Pristiyono Pristiyono; Muhammad Ali Al Ihsan (Quantitative Economics and Management Studies, 2023)
Live streaming marketing is a new trend that is attracting more and more people around the world. This allows businesses to reach their customers directly and provide them with a personalized experience without leaving their homes. For a company, it makes sense to use a live streaming marketing platform like TikTok because it helps them connect with their audience easily. This study aims to examine the driving factors that cause consumers to make purchases through the TikTok Shop application. This study uses a quantitative approach and the respondents in this study are students who have made purchases through the TikTok Shop application. Respondents in this study were 100 respondents. Data was collected using a questionnaire which was distributed online to consumers via the Google form. The results of the study indicate that the variables in this study have a positive and significant influence on consumer buying interest. From this research, sellers get inspiration in an effort to increase consumer buying interest. This research also contributes to the marketing literature and consumer behavior.